2017
DOI: 10.28926/briliant.v2i3.69
|View full text |Cite
|
Sign up to set email alerts
|

Keterkaitan Manajemen Pengetahuan dan Kecakapan Organisasional dengan Kinerja Inovasi serta Fungsi Mediasi Orientasi Kewirausahaan

Abstract: Penelitian ini bertujuan untuk memperkaya khasanah keilmuan manajemen dalam konteks kinerja inovasi. Penelitian ini adalah penelitian penjelasan dengan metode kuantitatif. Teknik pengambilan data yang digunakan adalah teknik sampel proporsional dengan jumlah responden 100 UKM sebagai syarat minimal dalam analisis Structural Equation Model (SEM). Sedangkan teknis data yang digunakan adalah Structural Equation Model (SEM) Analysis. Hasil penelitian menunjukkan bahwa terdapat keterkaitan antara manajemen pengetah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It was further explained that knowledge management can encourage innovation, which then has the potential to increase competitiveness. Previous research conducted by Dewi and Sugito (2017) on 100 SMEs in Batu City, East Java, Indonesia found that knowledge management affected innovation performance. Previous research by, Argote and Fahrenkopf (2016) and Kosaka and Nie (2020) confirms that effective knowledge management facilitates knowledge communication and exchange required in the innovation process, and further enhances innovation performance through the development of new insights and capabilities.…”
Section: Hypothesis Developmentmentioning
confidence: 96%
“…It was further explained that knowledge management can encourage innovation, which then has the potential to increase competitiveness. Previous research conducted by Dewi and Sugito (2017) on 100 SMEs in Batu City, East Java, Indonesia found that knowledge management affected innovation performance. Previous research by, Argote and Fahrenkopf (2016) and Kosaka and Nie (2020) confirms that effective knowledge management facilitates knowledge communication and exchange required in the innovation process, and further enhances innovation performance through the development of new insights and capabilities.…”
Section: Hypothesis Developmentmentioning
confidence: 96%